Nordic contributions in IS Research : 9th Scandinavian Conference on Information Systems, SCIS 2018, Odder, Denmark, August 5-8, 2018, Proceedings /: 9th Scandinavian Conference on Information Systems, SCIS 2018, Odder, Denmark, August 5-8, 2018, Proceedings. (2018) - Unknown
No abstract available